Do Migrants Improve Governance at Home? Evidence from a Voting Experiment - Batista, Catia (World Bank, 2013)
Can international migration promote better institutions at home by raising the demand for political accountability? A behavioral measure of the population's desire for better governance was designed to examine this question. A postcard was distributed to households promising that if enough postcards were mailed back, results from a survey module on perceived corruption would be published in the national media. Data from a tailored household survey were used to examine the determinants of this behavioral measure of demand for political accountability (undertaking the costly action of mailing the postcard) and to isolate the positive effect of international emigration using locality-level variation. The estimated effects are robust to the use of instrumental variables, including past migration and macro shocks in the destination countries. The estimated effects can be attributed mainly to migrants who emigrated to countries with better governance, especially migrants who return home.